Five dimensions of quality : a common sense guide to accreditation and accountability - Suskie, Linda A.; Ikenberry, Stanley O. (Stanley Oliver), 1935- (San Francisco, CA : Jossey-Bass, 2015)
'Meet calls for increased quality and understand accreditation expectationsAuthor Linda Suskie is internationally recognized for her work in higher education assessment, and she is a former vice president of a major regional accreditor. In Five Dimensions of Quality: A Common Sense Guide to Accreditation and Accountability in Higher Education she provides a simple, straightforward model for understanding and meeting the calls for increased quality in higher education ever-present in today's culture. Whether your institution is seeking accreditation or not, the five dimensions she outlines will help you to identify ways to improve institutional quality and demonstrate that quality to constituents.For those wading through the accreditation process, which has become more difficult in recent years due to increasing regulation and pressure for greater accountability, Suskie offers expert guidance on understanding the underlying principles of the expectations of accrediting bodies. Using the model presented here, which is much easier to understand than the sometimes complex resources provided by individual accrediting bodies, American colleges and universities can understand what they need to do to earn and maintain their regional accreditation as well as improve overall institutional quality for their students. You'll be able to: Identify ways to improve institutional quality Demonstrate the quality of your institution to internal and external constituents Avoid wasting time and energy on misguided institutional processes to comply with accreditation requirements By focusing on why colleges and universities should take particular actions rather than only on what those actions should be, Five Dimensions of Quality gives them the knowledge and strategies to prepare for a successful review. It is an ideal resource for leaders, accreditation committee members, and everyone on campus'--
'Provides American colleges and universities with clear guidance on how to satisfy the expectations of regional accreditors, and helps colleges or universities that are not seeking accreditation to identify ways to improve institutional quality and demonstrate that quality to constituents'--
Introduction : today's quality context. Why is American higher education under fire? ; Understanding American accreditation ; Quality : committing to excellence ; Why is this so hard? -- Dimension I : a culture of relevance. Integrity : doing the right thing ; Stewardship : ensuring and deploying resources responsibly -- Dimension II : a culture of community. A community of people ; Leadership capacity and commitment -- Dimension III : a culture of focus and aspiration. Purpose : who are you? why do you exist? ; Goals and plans : where are you going? how will you get there? ; Who is a successful student? ; Helping students learn and succeed -- Dimension IV : a culture of evidence. Gauging success ; Good evidence is useful ; Setting and justifying targets for success ; Transparency : sharing evidence clearly and readily -- Dimension V : a culture of betterment. Using evidence to ensure and advance quality and effectiveness ; Sustaining a culture of betterment -- Conclusion : integrating and advancing the five dimensions of quality. Demonstrating quality to accreditors ; Program reviews : drilling down into programs and services ; Where do we go from here? : a six-point agenda for ensuring and advancing quality.
Includes bibliographical references and index.
Keywords: Educational evaluation